A Histological Study of The Effect of Low Level Diode Laser Therapy on Wound Healing - Dawood, Monqith S.; Al-Habib, May Fadhal; Salman, Saif Dawood (Nahrain University College of Engineering Journal, 2009)
In this study we show an approach for wound healing process based on using of low level laser therapy, in order to enhance the healing rate of wounds. The low power laser (LPL) has been introduced also to solve problems associated with scar formation after completing the healing process.In this study the wound healing process rate was enhanced by using the illumination of 650 nm, 5 mW diode laser in CW and 2.5 mW maximum average power pulse modes with 1 MHz frequency and 50% duty cycle. The low power laser light biostimulates the wounded area which was made on the back of many mice. The healing process was histologically studied during fourteen days to find out the differences between the laser illuminated groups of wounds and other group of wounds (control). From the results, we found out that the pulse diode laser is more efficient than continuous diode laser in enhancing the wound healing process within shorter time.